2011
DOI: 10.1111/j.1601-5215.2011.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of cannabidiol and imipramine induces antidepressant-like effects in the forced swimming test and increases brain-derived neurotrophic factor levels in the rat amygdala

Abstract: Administration of cannabidiol and imipramine induces antidepressant-like effects in the forced swimming test and increases brain-derived neurotrophic factor levels in the rat amygdala.Objective: Cannabidiol is a chemical constituent from Cannabis sativa and it has multiple mechanisms of action, including antidepressant effects. The main objective of the present study was to evaluate behavioural and molecular effects induced by administration of cannabidiol and imipramine in rats. Methods: In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 72 publications
9
47
0
1
Order By: Relevance
“…Using nonstressed mice on a Swiss background, we replicated previous published findings that showed antidepressant-like effects of acute and repeated CBD treatment in the FST in mice (Zanelati et al, 2010) and rats (Réus et al, 2011). Here in, single CBD administration at doses of 3 and 10 mg/kg but not 30 mg/kg decreased immobility time in the TST.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using nonstressed mice on a Swiss background, we replicated previous published findings that showed antidepressant-like effects of acute and repeated CBD treatment in the FST in mice (Zanelati et al, 2010) and rats (Réus et al, 2011). Here in, single CBD administration at doses of 3 and 10 mg/kg but not 30 mg/kg decreased immobility time in the TST.…”
Section: Discussionsupporting
confidence: 88%
“…The common drawback of these studies, however, was that the animals received single intraperitoneal CBD injections. Only two studies of which we are aware have reported the antidepressant-like effects of chronic CBD administration (Réus et al, 2011;Campos et al, 2013). Campos et al (2013) tested the effects of repeated CBD administration (30 mg/kg for 14 days) on the behavioral consequences of chronic unpredictable stress (CUS) in C57/B6 mice, which included anhedonia and anxiety-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic CBD treatment reduced immobility time in mice, as did the prototype tricyclic antidepressant imipramine (Zanelati et al, 2010). Similar results were shown in mice submitted to the FST or the tail suspension test (TST) (El-Alfya et al, 2010; Réus et al, 2011; Schiavon et al, 2016). More recently, the antidepressant-like effect of CBD was detected in the olfactory bulbectomy (Linge et al, 2016) and learned helplessness models (Pereira et al, 2016).…”
Section: Mechanisms Of Cbd Effects In Neuropsychiatric Disorderssupporting
confidence: 70%
“…However, acute or sub-chronic CBD treatment failed to change hippocampal BDNF levels (Zanelati et al, 2010; Campos et al, 2012a). Réus et al (2011) reported similar results in three brain regions (PFC, hippocampus, and amygdala) after acute treatment with doses that induced antidepressant-like effects in rats submitted to the FST. Despite these negative results, BDNF involvement in the plastic changes induced by CBD cannot be ruled out.…”
Section: Mechanisms Of Cbd Effects In Neuropsychiatric Disordersmentioning
confidence: 72%
“…Given the enigmatic nature of this CBD, it would have only been appropriate to 'cast the net' far and wide to see what happens. Previous studies which have looked at the effect of chronic CBD on BDNF protein levels in mice and rats have also used a range of doses too (Réus et al 2011;Zanelati et al 2010). Secondly, in terms of the behavioural changes in the context of anxiety, it is unclear why only the total distance travelled was reported, and the amount of time spent in inner and outer zones of the activity boxes was not mentioned (Long et al 2009).…”
mentioning
confidence: 95%